2014
DOI: 10.7202/1023988ar
|View full text |Cite
|
Sign up to set email alerts
|

Revue des effets de la méditation de pleine conscience sur la santé mentale et physique et sur ses mécanismes d’action

Abstract: Les interventions basées sur la pleine conscience deviennent de plus en plus populaires. Le présent article présente une recension de ses effets sur la santé mentale et physique, des mécanismes d’action et des recherches en neurobiologie.Interventions based on mindfulness have become increasingly popular. This article reviews the empirical literature on its effects on mental and physical health, discusses presumed mechanisms of action as well as its proposed neurobiological underpinning. Mindfulness is associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(6 citation statements)
references
References 67 publications
0
3
0
3
Order By: Relevance
“…Numerous neurobiological mechanisms underpin the benefits of meditation for mental health, including attention and emotional regulation, cognitive re-evaluation and body awareness. Mindfulness meditation also holds benefit for physical health for people with MS by improving immune function and reducing inflammation [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous neurobiological mechanisms underpin the benefits of meditation for mental health, including attention and emotional regulation, cognitive re-evaluation and body awareness. Mindfulness meditation also holds benefit for physical health for people with MS by improving immune function and reducing inflammation [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hölzel et al (2011) found that the daily practice of 30 min of meditation increased the density of gray matter in the brain regions associated with empathy. Numerous studies have found this benefit (Greason and Cashwell, 2009;Birnie et al, 2010;De la Fuente-Anuncibay et al, 2019;Ngô, 2013;Shapiro et al, 1998). Nevertheless, several studies question this positive effect in the improvement of empathy when practicing mindfulness (Beddoe and Murphy, 2004;Dekeyser et al, 2008;Ridderinkhof et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Inicialmente, a aplicação do questionário PPS mostrou que, apesar de o grupo intervenção apresentar piores resultados em relação à percepção do estresse (32) do que o grupo controle (27,5), essa diferença não foi estatisticamente significante (p = 0,084) entre os estudantes antes do curso Redemed © (Tabela 3).…”
Section: Resultsunclassified
“…Entretanto, após os oito encontros semanais, o grupo intervenção apresentou melhora significativa (p = 0,030) por conta da redução na soma da pontuação fornecida pelo instrumento aplicado (24), enquanto os resultados do grupo controle permaneceram praticamente inalterados (27,5), como pode ser observado na Tabela 3.…”
Section: Resultsunclassified